SISTEM PENILAIAN UJIAN ESAI SECARA OTOMATIS DENGAN ALGORITMA TEXT MINING COSINE SIMILARITY PENUNJANG PEMBELAJARAN - Pane, Eddis Syahputra; Hardianto, Roki; Choriah, Wirdah (Universitas Lancang Kuning, 2024)
Currently, teachers must be able to utilize learning information technology in the form of online exams. This research will implement an online essay exam which is assisted by using a computer as a tool, better known as the Computer Assisted Test (CAT). The author developed a computer-based exam application for students at SMK Negeri 5 Pekanbaru. The exam questions that will be developed are online exam questions that can provide grades automatically. The questions that will be entered into the system are questions in essay form. Automatic scoring is carried out using the Case Folding and Tokenizing, Filtering, Stemming, Analyzing with Cosine similarity assessment stages. Exam participants' answers will also be searched for basic words using the results of extracting the basic words in the answer key and students' answers will be compared using Cosine similarity. The modeling process is carried out by developing existing models by adapting the real-time concept to be planned. The model obtained is the text stemming process and the process of extracting words from the answers carried out on client computers (teachers and students) and processing the answers and comparing the answers with the answer key. The modeling used is Waterfall and the analysis uses UML (Unified Modeling Language). This system was created using the PHP programming language, MySql database